Сутність та зміст правових форм забезпечення охорони праці поліцейських - Клочко, І. О.; Klochko, I. O. (Юридична наука. - 2020. - № 9 (111). - С. 209-215, 2020)
Виокремлено та надано характеристику наступним формам забезпечення охорони праці поліцейських: нормотворчість, правореалізація, правозастосування. Обґрунтовано важливість та необхідність законодавчого закріплення окреслених форм забезпечення охорони праці працівників Національної поліції України. Наголошено, що правові форми забезпечення охорони праці поліцейських спрямовані на те, щоб створити належне підґрунтя для роботи суб’єктів, які уповноважені здійснювати свою діяльність у відповідному напрямку. Саме за їх допомогою створюються умови, за яких всі сторони відповідних правовідносин будуть належним чином виконувати покладені на них обов’язки у сфері охорони праці поліцейських.

The article, based on the analysis of the scientific views of scientists and the norms of the current legislation, singles out and characterizes the following forms of ensuring the labor protection of police officers: rule-making, law enforcement, law enforcement. The well-founded importance and necessity of legislative consolidation of the forms of ensuring occupational health and safety of employees of the National Police of Ukraine outlined in the article are substantiated. It was found that the implementation of legal norms as a special process can be considered from the objective and subjective side. The objective side of the implementation of the norms of law is the performance of lawful acts in the places and in the terms stipulated by the norms of the law. The subjective side reveals the subject’s attitude to legal requirements and the state of his will at the time of performing actions required by law. After all, when the desire to ensure compliance of one’s behavior with legal requirements disappears, the process of implementing the right ceases. The process of implementation of legal norms is not limited to the legitimate behavior of legal entities in the form of compliance, implementation, and use, but has a more comprehensive and multifaceted nature, which includes, first of all, legal mechanisms for ensuring the implementation of the law. It was concluded that the legal forms of ensuring labor protection of police officers are aimed at creating a proper basis for the work of subjects who are authorized to carry out their activities in the relevant direction. In addition, it is with their help that conditions are created under which all parties to the relevant legal relationship will properly fulfill their duties in the field of labor protection of police officers. In view of the above, we consider it expedient to enshrine at the legislative level the list of the forms of ensuring labor protection of police officers outlined by us.

Выделена и дана характеристика следующим формам обеспечения охраны труда полицейских: нормотворчество, правореализация, правоприменение. Обоснованы важность и необходимость законодательного закрепления очерченных форм обеспечения охраны труда работников Национальной полиции Украины. Отмечено, что правовые формы обеспечения охраны труда полицейских направлены на то, чтобы создать надлежащую основу для работы субъектов, уполномоченных осуществлять свою деятельность в соответствующем направлении. Именно с их помощью создаются условия, при которых все стороны соответствующего правоотношения будут должным образом выполнять возложенные на них обязанности в сфере охраны труда полицейских.
The essence and content of legal forms of labor protection of police officers
Клочко, І. О. Сутність та зміст правових форм забезпечення охорони праці поліцейських / Клочко І. О. // Юридична наука. - 2020. - № 9 (111). - С. 209-215. - DOI: https://doi.org/10.32844/10.32844/2222-5374-2020-111-9.26.
Клочко , І. О. (2020). СУТНІСТЬ ТА ЗМІСТ ПРАВОВИХ ФОРМ ЗАБЕЗПЕЧЕННЯ ОХОРОНИ ПРАЦІ ПОЛІЦЕЙСЬКИХ. Юридична наука, (9 (111), 209–215. https://doi.org/10.32844/10.32844/2222-5374-2020-111-9.26.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; працівники поліції; police officers; работники полиции; охорона праці; occupational health; охрана труда; правова форма; legal form; правовая форма; нормотворчість; rule-making; нормотворчество; правозастосування; law enforcement; правоприменение; правореалізація; правореализация